Q: 89 plus 2t equals 10t plus 25?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

12(t+6)+8=4(2t-1)+2t 12t+72+8=8t-4+2t 12t-2t-8t=-72-8-4 2t=-84 2t/2=84/2 t=42

3r + 3r + 2t = 6r + 2t

Rearranging the the equation to make c the subject:- c = kVp-2t

R = S + 2T S = 3T .... substitute R = (3T) + 2T R = 5T

4t +7

Related questions

75+2t=100-2t 4t=25 t=6.25 So t is 6.25 or 25/4.

2t

In 2t+8 19

It is an expression that can be simplified to 10-10t.

12(t+6)+8=4(2t-1)+2t 12t+72+8=8t-4+2t 12t-2t-8t=-72-8-4 2t=-84 2t/2=84/2 t=42

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

24

(t+h)(x+2)

3r + 3r + 2t = 6r + 2t

Heyy, For this question, we first need to add 2t to both sides of the equation to get: 75 + 4t = 100 Now, subtract 75 from both sides of the equation to get: 4t = 25 At this time, divide both sides by 4 to get t alone and get: t = 25 / 4 OR 6.25 FINAL ANSWER = t=6.25

Rearranging the the equation to make c the subject:- c = kVp-2t

R = S + 2T S = 3T .... substitute R = (3T) + 2T R = 5T